Schlemm's canal is a unique vessel with a combination of blood vascular and lymphatic phenotypes that forms by a novel developmental process. - Krishnakumar Kizhatil (Public Library of Science (PLoS), 2014)
Schlemm's canal (SC) plays central roles in ocular physiology. These roles depend on the molecular phenotypes of SC endothelial cells (SECs). Both the specific phenotype of SECs and development of SC remain poorly defined. To allow a modern and extensive analysis of SC and its origins, we developed a new whole-mount procedure to visualize its development in the context of surrounding tissues. We then applied genetic lineage tracing, specific-fluorescent reporter genes, immunofluorescence, high-resolution confocal microscopy, and three-dimensional (3D) rendering to study SC. Using these techniques, we show that SECs have a unique phenotype that is a blend of both blood and lymphatic endothelial cell phenotypes. By analyzing whole mounts of postnatal mouse eyes progressively to adulthood, we show that SC develops from blood vessels through a newly discovered process that we name "canalogenesis." Functional inhibition of KDR (VEGFR2), a critical receptor in initiating angiogenesis, shows that this receptor is required during canalogenesis. Unlike angiogenesis and similar to stages of vasculogenesis, during canalogenesis tip cells divide and form branched chains prior to vessel formation. Differing from both angiogenesis and vasculogenesis, during canalogenesis SECs express Prox1, a master regulator of lymphangiogenesis and lymphatic phenotypes. Thus, SC development resembles a blend of vascular developmental programs. These advances define SC as a unique vessel with a combination of blood vascular and lymphatic phenotypes. They are important for dissecting its functions that are essential for ocular health and normal vision.